Engaging schools in diagnosis and treatment of malaria: Evidence of sustained impact on morbidity and behavior - Macnab, Andrew John; Mukisa, Ronald; Mutabazi, Sharif; Steed, Rachel (Global Health Management Journal, 2017)
Background:  In low and middle income countries (LMICs) teachers send home children found sick in class devolving subsequent care to parents; where malaria is endemic, morbidity is high as the most parents fail to access WHO-endorsed rapid diagnostic testing (RDT and prompt treatment with artemisinin combination therapy (ACT). Consequently malaria is the principal reason a child misses school; so, we trained teachers to use RDT to evaluate all sick pupils and give ACT promptly to those positive.Aims: Pre, intra and post intervention evaluation of impact of using the WHO Health Promoting School (HPS) model to empower teachers to provide RDT and ACT and engage and inform pupils about malaria in 4 schools in rural Uganda.Methods: Documenting duration of absence from school as a surrogate measure for morbidity and change in children’s knowledge and reported behaviors regarding malaria. Pre-intervention (year 1) baseline evaluation of days of absence and children’s malaria knowledge/behavior; Intervention (year 2) trained teachers administered RDT in all sick children and treated those positive with ADT; Post-intervention (end of year 3) after schools independently continued RDT/ACT and education on malaria.Results: Pre-intervention <1:5 pupils had basic knowledge about malaria (caused by mosquitos; can be prevented; requires rapid diagnosis and prompt medication). In year 1: 953 of 1764 pupils were sent home due to illness. Mean duration of absence was 6.5 (SD 3.17) school days. In year 2: 1066 of 1774 pupils were sick, all had RDT, 765/1066 (68%) tested positive and received ACT; their duration of absence fell to 0.59 (SD 0.64) school days (p<0.001). By year 2 all children knew the signs and symptoms of malaria and had essential epidemiological knowledge. Twelve months post intervention the universality of this knowledge had been sustained and the whole-school focus on malaria continued. Children reported better health, more consistent attendance and improved academic achievement, and had become proactive in prevention strategies; 6% fewer tested positive for malaria; and key health knowledge was being passed to new pupils.Conclusion: Teacher administered RDT/ACT reduced child morbidity from malaria significantly; essential knowledge was generated and new health practices acquired that changed behaviors. Our WHO HPS model is applicable to other LMICs where malaria is endemic and morbidity high.